Pengaruh Pemberian Poc Limbah Air Lele dan Pupuk Npk Mestibiru 16-16-16 Terhadap Tanaman Cabai Rawit (Capsicum Frutescens) - Romadani Saragih; Yudi Triyanto; Badrul Ainy Dalimunthe (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2021)
Saragih, Romadani "The Effect of Giving POC Waste of Catfish Water and Mestibiru NPK Fertilizer 16-16-16 Against the Rawit (Capsicum frutescens) Chilli PlantCatfish wastewater is often considered to be useless even though catfish water waste is very beneficial for plants. Especially if it is managed well like fermentation. If it has been managed, it can be a very useful POC. in testing the water of male fish in school, I conducted a study with cayenne pepper which was carried out in the agrtechnology experimental field of labuhanbatu university. This study used a randomized block design with a combination of NPK 16-16-16 Mestibiru fertilizer. In this study also observed a comparison of the provision of POC catfish water waste and NPK 16-16-16 Mestibiru. The results of the comparison with the treatment of POC pemebrian catfish waste water and NPK 16-16-16 Mestibiru POC pemebrian better. However, the best results in the research were the combination treatment of liquid oragnik fertilizer from catfish water waste with NPK 16-16-16 Mestibiru fertilizer getting the best results.Keyword : POC, Catfish Wasterwater, (NPK 16-16-16)